Theoretical investigation of structure and magnetic property of cubic MgFe2O4 - B, Khongorzul; N, Tsogbadrakh; D, Sangaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
Spinel type ferrites are of interest for many applications to their magnetic ion occupation induced magnetic phase transition. We consider the stability of ground states and magnetic property of normal, half and full inversed spinel structures for cubic MgFe2O4 phase using the first - principles method within the framenwork of density functional theory with on site correction for Coulomb interaction (GGA + U + J0). We have predicted the lattice parameters, magnetic moments of magnetic ions and compared with the results of x - ray diffraction and neutron scattering measurements. PACS numbers: 75.10.Dg, 75.50.Gg